MECP2 promotes cell proliferation by activating ERK1/2 and inhibiting p38 activity in human hepatocellular carcinoma HEPG2 cells - Zhao, L. Y.; Zhang, J.; Guo, B.; Yang, J.; Han, J.; Zhao, X. G.; Wang, X. F.; Liu, L. Y.; Li, Z. F.; Song, T. S.; Huang, C. (Cellular and Molecular Biology, 2013)
Hepatocellular carcinoma (HCC) is the third leading cause of cancer-related death worldwide and currently represents the leading cause of death amongst cirrhotic patients, but the mechanisms remain unknown. In this experiment, we investigated the expression of Methyl CpG-binding protein 2 (MeCP2) in HCC, the effect of MeCP2 on the proliferation of human HCC HepG2 cells, and the activation of mitogen-activated protein kinases (MAPKs) signaling pathways. The results showed that MeCP2 expression levels was higher in human HCC tissue than normal hepatocellular tissue, and MeCP2 siRNA reduced the proliferation of HCC HepG2 cells by decreasing cell activity and cell division in vitro. After MeCP2 siRNA treatment, the proportion of G1/G0 phase cells increased, but the proportion of S and G2/M phase cells decreased, indicative of G1/G0 cell cycle arrest. Furthermore, the proportions of early and late apoptosis in HCC HepG2 cells were enhanced after MeCP2 siRNA treatment. It was also found that activation of extracellular signal-regulated protein kinase (ERK) and p38 signaling pathways were involved in the proliferation of HepG2 cells. After MeCP2 siRNA treatment, p-ERK1/2 levels decreased, but p-p38 levels increased. Our findings demonstrated that MeCP2 promoted the proliferation of human HCC HepG2 cells with activation of ERK1/2 signaling pathways, suggesting a novel mechanism for pharmacological study of treatment for human HCC.